An Outbreak of Pseudomonas Mastitis in Dairy Cows - Osborne, A. D. (1981)
An outbreak of mastitis in a dairy herd is described in which the causative organism was Pseudomonas aeruginosa. Cases occurred either in dry cows or in animals which had very recently calved. The fact that all four quarters were involved is a very strong indication that the bacteria had been introduced in the dry cow therapy.